Hypoxia-ameliorated photothermal manganese dioxide nanoplatform for reversing doxorubicin resistance - Chen, Zhenzhen; Liu, Zhihong; Zhang, Qian; Huang, Sheng; Zhang, Zaizhong; Feng, Xianquan; Zeng, Lingjun; Lin, Ding; Wang, Lie; Song, Hongtao (Frontiers in Pharmacology, 2023)
Drug resistance is a huge hurdle in tumor therapy. Tumor hypoxia contributes to chemotherapy resistance by inducing the hypoxia-inducible factor-1α (HIF-1α) pathway. To reduce tumor hypoxia, novel approaches have been devised, providing significant importance to reverse therapeutic resistance and improve the effectiveness of antitumor therapies. Herein, the nanosystem of bovine serum albumin (BSA)-templated manganese dioxide (MnO2) nanoparticles (BSA/MnO2 NPs) loaded with doxorubicin (DOX) (DOX-BSA/MnO2 NPs) developed in our previous report was further explored for their physicochemical properties and capacity to reverse DOX resistance because of their excellent photothermal and tumor microenvironment (TME) response effects. The DOX-BSA/MnO2 NPs showed good biocompatibility and hemocompatibility. Meanwhile, DOX-BSA/MnO2 NPs could greatly affect DOX pharmacokinetic properties, with prolonged circulation time and reduced cardiotoxicity, besides enhancing accumulation at tumor sites. DOX-BSA/MnO2 NPs can interact with H2O2 and H+ in TME to form oxygen and exhibit excellent photothermal effect to further alleviate hypoxia due to MnO2, reversing DOX resistance by down-regulating HIF-1α expression and significantly improving the antitumor efficiency in DOX-resistant human breast carcinoma cell line (MCF-7/ADR) tumor model. The hypoxia-ameliorated photothermal MnO2 platform is a promising strategy for revering DOX resistance.